Proveniência sedimentar e relações entre o Grupo Macaúbas e o Complexo Jequitinhonha na divisa Minas Gerais/Bahia - Fernando Estevão Rodrigues Crincoli Pacheco (2022)
The precursor basin of the Araçuaí – West Congo Orogenic System (AWCO) formed a large gulf within the São Francisco – Congo Paleocontinent (SFCP), where sedimentary successions ascribed to the Jequitinhonha Complex and Macaúbas Group were deposited in the Neoproterozoic. This precursor basin system comprises an aborted continental rift of Early Tonian age and a Cryogenian rift that evolved to ocean-floor spreading up to the Early Ediacaran. The Jequitinhonha Complex is an extensive metasedimentary unit located in the northeastern Araçuaí Orogen, consisting of Al-rich paragneiss (kinzigite), sillimanite-graphite gneiss and associated economic deposits of flake graphite, quartzite and lenses of calc-silicate rock, metamorphosed to upper amphibolite or granulite facies around 570–550 Ma. The Macaúbas Group is the best preserved unit of the precursor basin of the Araçuaí Orogen, has a volcano-sedimentary sequence divided into three successions in relation to the presence of glaciogenic diamictites: i) a diamictite-free preglacial succession deposited in fluvial to shallow marine systems; ii) successions rich in glaciogenic diamictites; and iii) a post-glacial succession containing fine-grained turbidites and sedimentary exhalative deposits interleaved with metamafic and meta-ultramafic rocks that are interpreted as remnants of a Neoproterozoic oceanic lithosphere. U-Pb (LA-MC-ICP-MS) data of 110 detrital zircon grains from the paleosome of a migmatitic paragneiss of Jequitinhonha Complex coupled with Lu-Hf in zircon (LA-MC-ICP-MS) data for 106 zircon grains suggest the following sources: Neoarchean to Orosirian grains were sourced from the SFCP basement, Early Tonian grains from the anorogenic magmatic province, and Cryogenian to Early Ediacaran grains were provided by the Southern Bahia Alkaline Province and Rio Doce magmatic arc. U-Pb (LA-MC-ICP-MS) data of 189 detrital zircon grains of the Lower Chapada Acauã Formation and of 104 zircon crystals from a granitic clast of the diamictite suggests a contribution from the Archean and Paleoproterozoic basement of the São Francisco – Congo paleocontinent and metamorphic complexes, from the Mesoproterozoic intrusive and volcanic rocks of São Francisco Craton, and from the Tonian Salto da Divisa Suite. The sedimentation of Jequitinhonha Complex protoliths developed from the Cryogenian to Early Ediacaran. The absence of late Cryogenian grains in lower Chapada Acauã Formation leaves open the question of whether this formation is related to the Sturtian, to the Marinoan, or both Snowball glaciations.